Quality of life from a randomized trial of laparoscopic or open liver resection for colorectal liver metastases. Issue 10 (19th July 2019) - Fretland, Å A; Dagenborg, V J; Waaler Bjørnelv, G M; Aghayan, D L; Kazaryan, A M; Barkhatov, L; Kristiansen, R; Fagerland, M W; Edwin, B; Andersen, M H
Abstract: Background: Most treatments for cancer cause a decline in patients' health-related quality of life (HRQoL). Limiting this decline is a universal goal for healthcare providers. Using minimally invasive instead of open surgical techniques might be one way to achieve this. The aim of this study was to compare postoperative HRQoL after open and laparoscopic liver resection. Methods: This was a predefined substudy of an RCT comparing open with laparoscopic liver resection. Patients with colorectal liver metastases were assigned randomly to open or laparoscopic parenchyma-sparing liver resection. HRQoL was assessed with the Short Form 36 questionnaire at baseline, and 1 and 4 months after surgery. Results: A total of 280 patients were randomized, of whom 273 underwent surgery (129 laparoscopic, 144 open); 682 questionnaires (83.3 per cent) were available for analysis. One month after surgery, patients in the laparoscopic surgery group reported reduced scores in two HRQoL domains (physical functioning and role physical), whereas those in the open surgery group reported reduced scores in five domains (physical functioning, role physical, bodily pain, vitality and social functioning). Four months after surgery, HRQoL scores in the laparoscopic group had returned to preoperative levels, whereas patients in the open group reported reduced scores for two domains (role physical and general health). The between-group difference was statistically significant in favour of laparoscopy for four domains after 1 month (role physical, bodily pain, vitality and social functioning) and for one domain after 4 months (role physical). Conclusion: Patients assigned to laparoscopic liver surgery reported better postoperative HRQoL than those assigned to open liver surgery. For role limitations caused by physical health problems, patients in the laparoscopic group reported better scores up to 4 months after surgery. Registration number: NCT01516710 (http://www.clinicaltrials.gov ). Graphical Abstract: In this substudy of an RCT, patients assigned to laparoscopic liver surgery reported better postoperative health-related quality of life than patients assigned to open liver surgery. Laparoscopic approach improves quality of life